ANALYSIS OF THE PROCESS OF LOSS OF DRINKING WATER FOR CITIES DONETSK OBLAST - , Л. Г., Л. В., А. И. (Municipal economy of cities. Series: «Economy science», 2013)
The calculation and analysis of individual technological standards for the use of drinking water for the cities of Donetsk region. Recommended qualitatively new approaches to the maintenance of water supply systems.